Operation and Applications of Rice Hull Gasifier-Combustors - F.D. Jr., Vinluan; Santos, A.; Pacatang, L.; Canayon, A.; Valdecanas, M.; Balais, W.; Sungabea, E.; Barnuevo, E.; Lontok, N.; Padua, R.; Aquino, J.; Carandang, A. (Philippine Engineering Journal, 2021)
The gasifier-combustors operate on the principle of the (unreadable) hatch type gasifier. The gas generated in the reactor, which has a heating value of 3,900-4,000 kJ/SCM is ignited in the gas exit or piped to a thermal equipment. Two (2) realtors with internal diameters 45.72 cm (drum-size) and a large (square) unit with 105 cm. x 105 cm. in cross section were used. The drum-size gasifier-combustors were to fire clay bricks in a small wood-fired kiln. Four (4) drum-size units were also used to fire bricks in a shuttle kiln. The result: show that a temperature of 740-850 C within the kiln was attained in 8-hour firing period. The laboratory tests on the fired products revealed that their properties are within set standards.  Initial tests on the use of the drum size units in a food drier (indirect drying) and in a grain drier (direct) show that the gasifier-combustor can maintain the required temperature within the drying chamber or plenum. The economic projections show that it is economically feasible to adopt the gasifier combustor for food and grain drying. Other agro wastes such as coconut husks, corn cobs and coffee hulls were also tested successfully as fuels in the drum-size units.  The large unit which is capable of delivering 1 million kJ/hr will be attached to a 6cm. Wood-fired kiln for brick firing. As envisioned, this type of equipment will be used as heat source of a boiler for power generation and process heat.